RELATIONSHIP OF KNOWLEDGE POWER TO THE CAR SHAPED THRONE IN PALUANG TEMPLE, NUSA PENIDA, KLUNGKUNG BALI - Gede Suyoga, I Putu (International Conference on Cultural Studies, 2018)
The design of throne cars shaped is a new phenomenon in the architecture of Balinese worship. This unique phenomenon can be seen in Paluang Temple Nusa Penida. Two car shaped shrines Beatle VW and Jimny Jeep, dedicated to worship Ida Betara Ratu Gede Sakti Hyang Mami and his retinue. This study aims to reveal the power of knowledge relation on the design of the car shaped shrine. This study uses qualitative method with analytical descriptive approach. Data collection with observation and documentation. Informant determination was done by purposive sampling. Data analysis is based on power of knowledge relation, and power of discipline theory. The findings of this study reveal the strong power of knowledge relation in the myths developed by organic intellectuals (spiritual and indigenous leaders). The knowledge behind the myth is captured and developed as a power through media car shaped throne. The power relations discipline, work to discipline the body of Karang Dawa village community in the practice of worship in both shrines and other shrines in Paluang Temple, as the fulfillment of desire and expectation. The car shaped throne is a religious sign. In this millennial era, the globalization of media information has a lerated and expanded the consumption of the sign, not only limited in the area of Nusa Penida Bali, but has expanded throughout the world, through the role of capitalist actors who capture the knowledge behind the existence of the two cars shaped shrine to be a power in commercial realm.